KORELASI PENGETAHUAN PERSONAL HYGIENE DAN PERILAKU SAAT MENSTRUASI PADA REMAJA PUTRI - R. Latuamury, Sitti (STIKES Pasapua Ambon, 2023)
Introduction: Adolescence is a dynamic developmental phase in a person's life. This period is the transition from childhood to adulthood, marked by physical, mental, emotional, and social development. Objective: The general purpose is to determine the relationship between personal hygiene knowledge and behavior during menstruation in Talita Kumi Sector One Waai Village, Central Maluku Regency adolescent girls. Methods: The research method used is an analytical survey with a cross-sectional study design. Sampling using a total sampling technique with a total of 38 respondents. Bivariate analysis using the chi-square statistical test. Results: The results of the research obtained were young women in Talitakumi Sector 1 Waai village, Central Maluku regency, who had good knowledge of as many as 13 respondents with a percentage (34.2%), while young women who had poor knowledge of as many as 25 respondents (65.8%). Adolescents who have good behavior as many as 26 respondents with a percentage (68.4%), while adolescents who have poor behavior as many as 12 respondents (31.6%). The relationship of knowledge with adolescent behavior during menstruation in the talitakumi1 sector of Waai Village is a statistical test at a value of p = 0.064. In other words, the p-value in this study is more significant than 0.05, concluding that there is no relationship between knowledge and adolescent behavior during menstruation. Recommendation: this study can be a reference for readers to do personal hygiene during menstruation as a form of education for preventing diseases caused by bacteria.